Computation of ankle torque in different strategies of landing by dynamic modeling - Mirtavoosi, S.; Lenjannejadian, S.; Khayambashi, K.; Salehi, H.; Mahdieh, L. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Ankle joint injury often occurs in sports. The purpose of this study was to compute ankle torque under different strategies of landing using human body movement simulation during landing for males and females. Kinematic and kinetic data were given to model and ankle torque under three strategies of landing was computed. Results showed that in first strategy there was a minimum value of peak ankle torque for both males and females. In second and third strategies by increasing plantar flexion of ankle, peak ankle torque was increased for both males and females. Results were in agreement with previous experimental investigations.